Functional Status of Hypothalamic–Pituitary–Thyroid and Hypothalamic–Pituitary–Adrenal Axes in Hospitalized Schizophrenics in Shanghai - Zhu, Yuncheng; Ji, Haifeng; Tao, Lily; Cai, Qing; Wang, Fang; Ji, Weidong; Li, Guohai; Fang, Yiru (Frontiers in Psychiatry, 2020)
Objective: Neuroendocrine dysfunction is related to the pathogenesis of mental disorders, but conclusions from clinical research lack consistency. We aimed to investigate the neuroendocrinal pathophysiology and its correlation with clinical symptoms in patients with schizophrenia. Methods: The present cross-sectional study included 486 inpatients with schizophrenia admitted at a psychiatric hospital in Shanghai within one year, and 154 healthy controls (HC) matched on age and gender. The serum haemoconcentrations of thyroid-stimulating hormone (TSH), total triiodothyronine (TT3), total thyroxine (TT4), free triiodothyronine (FT3), free thyroxine (FT4), adrenocorticotrophic hormone (ACTH), and cortisol (COR) were measured via electrochemical luminescence immunoassay. Pathophysiological conversions of neuroendocrine were then associated with age, course of disease, and Positive and Negative Syndrome Scale (PANSS) scores using Pearson’s correlations. Results: When compared to HC, the schizophrenia group showed elevated ACTH and COR levels, and decreased TT3 and TT4 levels (p’s<0.05). First-episode patients showed lower TSH and higher FT3 and FT4 (p’s<0.05) compared to recurrent patients. Female patients showed higher TSH and lower TT3, FT3 and ACTH levels (p’s<0.05) compared to males. PANSS scores were positively correlated with COR levels (r=0.219, p<0.05). Conclusions: Decreased TT3 and TT4 and elevated ACTH and COR levels appear to be associated with schizophrenia symptoms. The chronic recurrent trait of schizophrenia may cause long-term effects on FT3 and FT4 while changes in thyroid, and adrenal function as a result of mental disorder varied with gender. Symptom severity in hospitalized patients may directly impact COR levels.